2011
DOI: 10.1016/j.biopsych.2011.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Cytokine Alterations in Schizophrenia: Clinical Status and Antipsychotic Effects

Abstract: Background Schizophrenia is associated with immune system dysfunction, including aberrant cytokine levels. We performed a meta-analysis of these associations, considering effects of clinical status and antipsychotic treatment following an acute illness exacerbation. Methods We identified articles by searching PubMed, PsychInfo, and Institute for Scientific Information and the reference lists of identified studies. Results Forty studies met the inclusion criteria. Effect sizes were similar for studies of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

82
1,238
19
33

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,502 publications
(1,372 citation statements)
references
References 104 publications
82
1,238
19
33
Order By: Relevance
“…The causes of white matter abnormalities in schizophrenia remain unclear. One of the possibilities explaining the link between tryptophan level and FA may in part be related to evidence of chronic inflammation in schizophrenia (Miller et al, 2011;Upthegrove et al, 2014). Proinflammatory cytokines, interferon-γ in particular, upregulate IDO, one of the ratelimiting enzymes involved in conversion of tryptophan to kynurenine .…”
Section: Discussionmentioning
confidence: 99%
“…The causes of white matter abnormalities in schizophrenia remain unclear. One of the possibilities explaining the link between tryptophan level and FA may in part be related to evidence of chronic inflammation in schizophrenia (Miller et al, 2011;Upthegrove et al, 2014). Proinflammatory cytokines, interferon-γ in particular, upregulate IDO, one of the ratelimiting enzymes involved in conversion of tryptophan to kynurenine .…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of data has demonstrated higher levels of proinflammatory markers, such as cytokines, in cerebrospinal fluid and plasma in patients across disease stages of schizophrenia (3,47). In the brain, these signaling molecules are mainly released by microglia and astrocytes, which have key roles in the immune response (9).…”
Section: Meta-analysis Of Tspo In Patients With Psychosismentioning
confidence: 99%
“…As for BPD, peripheral IL-2, IL-4 and IL-6 are found to be increased in manic episodes (Brietzke et al, 2011) whereas another meta-analysis revealed significant elevation of soluble interleukin (IL)-2 receptor (sIL-2R), TNF-a, soluble tumor necrosis factor receptor type 1 (sTNFR1) and soluble interleukin (IL)-6 receptor (sIL-6R) (Munkholm et al, 2013). In the case of schizophrenia, TNF-a, IFN-g, IL-12 and IL-2 are consistently elevated in chronic schizophrenic patients, while IL-1b, IL-6 and TGF-b correlate positively with disease activity (Miller et al, 2011).…”
Section: Purinergic Regulation Of Neuroinflammation In Cns Disordersmentioning
confidence: 99%